A comparison of dispersion models for the LNG dispersion at port of Koper, Slovenia - Gerbec, Marko; Vidmar, Peter; Pio, Gianmaria; Salzano, Ernesto (Safety science, 2021)
•Characterization of LNG dispersion via Unified Dispersion Model and CFD models.•Identification of possible releasing points in the port of Koper.•Evaluation of the effect of evaporation rates on CFD estimations.•Assessment of the effects of turbulence sub-model on CFD. The challenges of ensuring green shipping and green ports force ports to adequately and safely implement engineered systems for the distribution and supply of LNG in port areas that meet the requirements of Seveso Directive. As the process of LNG bunkering is only seemingly similar to classical oil bunkering or liquid cargo, the handling of the technical and safety challenges is much more subject to investigation. In this work, the dispersion part of the consequences of LNG release, pooling, evaporation and dispersion during the future bunkering operation in the port of Koper, Slovenia, where the populated area (city) is located in close proximity. We follow the comparison of three different tools, namely the model Unified Dispersion Model (UDM) implemented by the software PHAST from DNV-GL® and two CFD (FDS - Fire Dynamics Simulator from NIST and Ansys Fluent®) in the same case scenario. Geometry, initial and boundary conditions are assumed to be the same as far as possible according to the limitations of the respective software tools. The simulation tools are first applied to a flat terrain model and later the models of CFD are compared, including the 3D geometry of the dock site in real size, with two relevant wind directions. The effects of evaporation rates on water and turbulence on CFD estimates are also given and numerically tested. The results of the applied models provide valuable information for further establishment of similar LNG leakage and dispersion models for simulation in ports or similar facilities.